Islamic Rational Choice during COVID-19: Contest of Opinions and Practices in Islam in Indonesia - Mahyudin, M. Alfan Alfian (The international journal of religion and spirituality in society, 2022)
In response to the COVID-19 pandemic, the Indonesian government has established policies based on scientific and rational considerations. The ministry of religion introduced policies that are scientific and rational so that they have an impact on changing Islamic worship procedures. These policies are fully supported by the Indonesian Muslim Scholar Council and various mainstream Islamic organizations, such as Muhammadiyah and Nahdlatul Ulama. This can be attributed to their moderate and accommodative attitude toward government policies. However, some Muslim scholars seem irrational, rejecting the existence of and dangers associated with COVID-19. Irrational attitudes are often expressed openly and become viral on social media. Meanwhile, the government and mainstream Islamic organizations are conducting intensive socialization and education that are rational and proactive in handling the COVID-19 pandemic. Sometimes, they change to the path of rational choice by supporting government policies so as not to trigger problems.